Beach volleyball serve type recognition - Cuspinera, L. P.; Uetsuji, S.; Morales, F. O.; Roggen, D. (ISWC '16: Proceedings of the 2016 ACM International Symposium on Wearable Computers, 2016)
We present results on beach volleyball serve recognition and classification from a wrist-worn gyroscope deployed with semi-professional beach volleyball players. We trained a template-based recognition system based on a Warping Longest Common Subsequence algorithm to spot serves, and potentially distinguish among 4 common serve types. This shows the potential of wearable technologies in beach volleyball, which could offer precise sport analytics.